2008
DOI: 10.1097/01.asw.0000305420.73597.d2
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Web-Based Training in Using the Braden Scale to Predict Pressure Sore Risk

Abstract: Web-based training alone may not ensure reliable, competent estimates of pressure-ulcer risk for patients at all risk levels. Other strategies, such as clinical practice with expert supervision, should be considered. Further research is needed to clarify the links between scoring Braden subscales correctly and selecting appropriate risk-based preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…7,8,24 The DMC Braden Scale Training module was designed specifically for the purpose of teaching RNs how to use the Braden Scale correctly to make PU risk assessments and select riskbased PU prevention interventions. 11,16,25 The module contains both training and testing content. Case study exemplars are used to test nurses' ability to make reliable Braden Scale risk assessments and select appropriate riskbased prevention interventions when working with case study data.…”
Section: Instrumentsmentioning
confidence: 99%
“…7,8,24 The DMC Braden Scale Training module was designed specifically for the purpose of teaching RNs how to use the Braden Scale correctly to make PU risk assessments and select riskbased PU prevention interventions. 11,16,25 The module contains both training and testing content. Case study exemplars are used to test nurses' ability to make reliable Braden Scale risk assessments and select appropriate riskbased prevention interventions when working with case study data.…”
Section: Instrumentsmentioning
confidence: 99%
“…The effect of this education on nurses' knowledge of pressure ulcer risk assessment and prevention 53,54 and its effect on the reliability and precision of pressure ulcer risk assessments 55 have been evaluated. However, the digital modules are not formatted in Adobe Flash programming (Adobe Systems, San Jose, California).…”
Section: ■ Backgroundmentioning
confidence: 99%
“…More recent research suggests that training on how to correctly use the Braden Scale is needed to improve the reliability of Braden Scale risk assessments made by RNs working in acute care hospitals. 3,[5][6][7] The fact that a nurse has used the Braden Scale for a long time does not mean that all of his or her pressure ulcer risk assessments are reliable. Research has shown that considerable room for improvement exists in the reliability of Braden Scale assessments made by nurses who regularly use the Braden Scale.…”
Section: Assessmentmentioning
confidence: 99%